Analysis of the Implementation of the Pomodoro Technique in Enhancing the Learning Concentration of Eighth-Grade Students - Gita Tausyah Sakinah; Agus Prasetyo Kurniawan; Astarika (Global Action and Education for Society, 2026)
This study aims to analyze the implementation of the Pomodoro Technique in teaching at the eighth-grade class of MTs Darul Ulum Waru and its impact on improving students’ concentration. The research employs a qualitative approach using a case study method. Data were collected through observation, interviews, and documentation. The findings reveal that the application of the Pomodoro Technique has a positive influence on students’ learning concentration and focus. The use of 25-minute study intervals followed by 5-minute breaks helps maintain students’ optimal attention, reduce boredom, and enhance time management during learning activities. Teachers play a crucial role in guiding the process, monitoring students’ time use, and ensuring that breaks are used effectively. Challenges encountered include limited face-to-face learning time, students’ initial adaptation to the interval system, and a lack of awareness regarding the importance of time management. Overall, the Pomodoro Technique proves to be an effective learning strategy for fostering a more focused, productive, and enjoyable learning environment in madrasah settings. With consistent implementation and proper teacher guidance, this technique has the potential to enhance learning quality and students’ academic performance.